Effect of High Altitude Environment on Pharmacokinetic and Pharmacodynamic of Warfarin in Rats - Zhang, Xiaojing; Mu, Hongfang; Zhong, Yan; Wang, Rong; Li, Wenbin (Current Drug Metabolism, 2024)
Background: High altitude environment affects the pharmacokinetic (PK) parameters of drugs and the PK parameters are an important theoretical basis for guiding the rational clinical use of drugs. Warfarin is an oral anticoagulant of the coumarin class commonly used in clinical practice, but it has a narrow therapeutic window and wide individual variation. However, the effect of high altitude environment on PK and pharmacodynamic (PD) of warfarin is unclear. Objective: The objective of this study is to investigate the effect of a high altitude environment on PK and PD of warfarin in rats. Method: Rats were randomly divided into plain group and high altitude group and blood samples were collected through the orbital venous plexus after administration of 2 mg/kg warfarin. Warfarin concentrations in plasma samples were determined by liquid chromatography-tandem mass spectrometry (LC-MS/MS) and PK parameters were calculated by the non-compartment model using WinNonlin 8.1 software. Meanwhile, the expression of PXR, P-gp and CYP2C9 in liver tissues was also determined by western blotting. The effect of high altitude environment on PD of warfarin was explored by measuring activated partial thromboplastin time (APTT) and prothrombin time (PT) values and then calculated international normalized ratio (INR) values based on PT. Results: Significant changes in PK behaviors and PD of warfarin in high altitude-rats were observed. Compared with the plain-rats, the peak concentration (Cmax) and the area under the plasma concentration-time curve (AUC) increased significantly by 50.9% and 107.46%, respectively. At the same time, high altitude environment significantly inhibited the expression of PXR, P-gp and CYP2C9 in liver tissues. The results of the PD study showed that high altitude environments significantly prolonged PT, APTT and INR values. Conclusion: High altitude environment inhibited the metabolism and increased the absorption of warfarin in rats and increased the effect of anticoagulant effect, suggesting that the optimal dose of warfarin for patients at high altitude should be reassessed.
Keywords: warfarin